What to Measure in Aneurysmal Subarachnoid Haemorrhage Research—An International Delphi Survey - Christopher R. Andersen; Justin Presseau; Bev Shea; Maria Luisa Marti; Madeline McCoy; Gordon Fernie; Lauralyn McIntyre; Anthony Delaney; Michaël Chassé; Victoria Saigle; Shawn Marshall; Dean A. Fergusson; et al. (Translational Stroke Research, 2025)

A multicentre evaluation and expert recommendations of use of the newly developed BioFire Joint Infection polymerase chain reaction panel - Kordo Saeed; Nusreen Ahmad-Saeed; Rachel Annett; Gavin Barlow; Lucinda Barrett; Sara E. Boyd; Nicola Boran; Peter Davies; Harriet Hughes; Gwennan Jones; Laura Leach; Maureen Lynch; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Septic arthritis is a serious condition with significant morbidity and mortality, routinely diagnosed using culture. The FDA has recently approved the rapid molecular BioFire® Joint Infection Panel (BJIP) for synovial fluid. We aimed to evaluate the BJIP compared to culture and its potential use in patient management. A multicentre retrospective evaluation of BJIP was conducted in the UK and Ireland. Positive percent agreement (PPA) and negative percent agreement (NPA) were calculated between the BJIP and routine culture. A multidisciplinary team (MDT) discussion addressing the optimal or potential case use of the assay practice was facilitated. Three hundred ninety-nine surplus synovial fluid samples (~ 70% from native joints) from eight centres were processed using BJIP in addition to routine culture. An increased yield of positive results was detected using BJIP compared to routine culture (98 vs 83), giving an overall PPA of 91.6% and overall NPA of 93% for the BJIP compared to culture results. The BJIP detected resistant markers and additional organisms that could influence antibiotic choices including Neisseria gonorrhoeae and Kingella kingae . The MDT agreed that the assay could be used, in addition to standard methods, in adult and children patients with specialist advice use based on local needs. Rapid results from BJIP were assessed as having potential clinical impact on patient management. Organisms not included in the panel may be clinically significant and may limit the value of this test for PJI.

Hydrology of peat estimated from near-surface water contents - Dimitre D. Dimitrov; Peter Lafleur; Oliver Sonnentag; Julie Talbot; William L. Quinton (Hydrological Sciences Journal, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Bright spots as climate‐smart marine spatial planning tools for conservation and blue growth - Ana M. Queirós; Elizabeth Talbot; Nicola J. Beaumont; Paul J. Somerfield; Susan Kay; Christine Pascoe; Simon Dedman; Jose A. Fernandes; Alexander Jueterbock; Peter I. Miller; Sevrine F. Sailley; Gianluca Sará; et al. (Global Change Biology, 2021)
Marine spatial planning that addresses ocean climate‐driven change (‘climate‐smart MSP’) is a global aspiration to support economic growth, food security and ecosystem sustainability. Ocean climate change (‘CC’) modelling may become a key decision‐support tool for MSP, but traditional modelling analysis and communication challenges prevent their broad uptake. We employed MSP‐specific ocean climate modelling analyses to inform a real‐life MSP process; addressing how nature conservation and fisheries could be adapted to CC. We found that the currently planned distribution of these activities may become unsustainable during the policy's implementation due to CC, leading to a shortfall in its sustainability and blue growth targets. Significant, climate‐driven ecosystem‐level shifts in ocean components underpinning designated sites and fishing activity were estimated, reflecting different magnitudes of shifts in benthic versus pelagic, and inshore versus offshore habitats. Supporting adaptation, we then identified: CC refugia (areas where the ecosystem remains within the boundaries of its present state); CC hotspots (where climate drives the ecosystem towards a new state, inconsistent with each sectors’ present use distribution); and for the first time, identified bright spots (areas where oceanographic processes drive range expansion opportunities that may support sustainable growth in the medium term). We thus create the means to: identify where sector‐relevant ecosystem change is attributable to CC; incorporate resilient delivery of conservation and sustainable ecosystem management aims into MSP; and to harness opportunities for blue growth where they exist. Capturing CC bright spots alongside refugia within protected areas may present important opportunities to meet sustainability targets while helping support the fishing sector in a changing climate. By capitalizing on the natural distribution of climate resilience within ocean ecosystems, such climate‐adaptive spatial management strategies could be seen as nature‐based solutions to limit the impact of CC on ocean ecosystems and dependent blue economy sectors, paving the way for climate‐smart MSP.

Transgene‐mediated skeletal phenotypic variation in zebrafish - Charles B. Kimmel; Alexander L. Wind; Whitney Oliva; Samuel D. Ahlquist; Charline Walker; John Dowd; Bernardo Blanco‐Sánchez; Tom A. Titus; Peter Batzel; Jared C. Talbot; John H. Postlethwait; James T. Nichols (Journal of Fish Biology, 2021)
When considering relationships between genotype and phenotype we frequently ignore the fact that the genome of a typical animal, notably including that of a fish and a human, harbours a huge amount of foreign DNA. Such DNA, in the form of transposable elements, can affect genome function in a major way, and transgene biology needs to be included in our understanding of the genome. Here we examine an unexpected phenotypic effect of the chromosomally integrated transgene fli1a‐F‐hsp70l:Gal4VP16 that serves as a model for transgene function generally. We examine larval fras1 mutant zebrafish ( Danio rerio ). Gal4VP16 is a potent transcriptional activator that is already well known for toxicity and mediating unusual transcriptional effects. In the presence of the transgene, phenotypes in the neural crest‐derived craniofacial skeleton, notably fusions and shape changes associated with loss of function fras1 mutations, are made more severe, as we quantify by scoring phenotypic penetrance, the fraction of mutants expressing the trait. A very interesting feature is that the enhancements are highly specific for fras1 mutant phenotypes, occurring in the apparent absence of more widespread changes. Except for the features due to the fras1 mutation, the transgene‐bearing larvae appear generally healthy and to be developing normally. The transgene behaves as a genetic partial dominant: a single copy is sufficient for the enhancements, yet, for some traits, two copies may exert a stronger effect. We made new strains bearing independent insertions of the fli1a‐F‐hsp70l:Gal4VP16 transgene in new locations in the genome, and observed increased severities of the same phenotypes as observed for the original insertion. This finding suggests that sequences within the transgene, for example Gal4VP16, are responsible for the enhancements, rather than the effect on neighbouring host sequences (such as an insertional mutation). The specificity and biological action underlying the traits are subjects of considerable interest for further investigation, as we discuss. Our findings show that work with transgenes needs to be undertaken with caution and attention to detail.

Over 75 years of zooplankton data from Australia - Claire H. Davies; Amelia J. Armstrong; Mark Baird; Frank Coman; Steven Edgar; Daniel Gaughan; Jack Greenwood; Felipe Gusmão; Natasha Henschke; J. Anthony Koslow; Sophie C. Leterme; A. David McKinnon; et al. (Ecology, 2014)
Zooplankton are the key trophic link between primary producers and fish in pelagic ecosystems. Historically, there are few zooplankton time series in Australia, with no data sets longer than two years prior to 2008. Here we compile 98 676 abundance records of more than 1000 zooplankton taxa from unpublished research cruises, student projects, published literature, and the recent Integrated Marine Observing System (IMOS). This data set covers the entire coastal and shelf region of Australia and dates back to 1938. Most records are for copepods, but there are also data for other taxa such as decapods, chaetognaths, thaliaceans, appendicularians, and cladocerans. Metadata are provided for each record, including dates, coordinates, and information on mesh size and sampling methods. To facilitate analysis across the multiple data sets, we have updated the species names according to the World Register of Marine Species (WoRMS) and converted units to abundance per cubic meter. These data will be valuable for studies of biodiversity, biogeography, impacts of climate change, and ecosystem health. We encourage researchers holding additional Australian zooplankton data to contact us and contribute their data to the data set so we can periodically publish updates.

Large group of pygmy right whales seen in a shelf upwelling region off Victoria, Australia - Peter C. Gill; Catherine M. Kemper; Matthew Talbot; Susie A. Lyons (Marine Mammal Science, 2008)

Separating the direct effect of hypoxia from the indirect effect of changes in cardiac output on the maximum pressure difference across the tricuspid valve in healthy humans - George M. Balanos; Nicholas P. Talbot; Peter A. Robbins; Keith L. Dorrington (Pflügers Archiv - European Journal of Physiology, 2005)

In vivo affinity of [18F]fallypride for striatal and extrastriatal dopamine D2 receptors in nonhuman primates - Mark Slifstein; Dah-Ren Hwang; Yiyun Huang; NingNing Guo; Yasuhiko Sudo; Raj Narendran; Peter Talbot; Marc Laruelle (Psychopharmacology, 2004)